(3GdNUGd GdYTQI GdJi LQHgG Cgd GdeMGSHIs - (3TgGH GdOjf CHh GdYHGS CMeO Hf CMeO Hf eMeO Hf YjSi GdHQfSi GdaGSis; (3CHh GdMSf Ydj Hf YHO Gddg Hf YHO GdLHGQ GdTGPdj GdeZQHj,J (B656 (3g` s ((3MSjf CMeOjf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi aJM dChdjGFg WQb GdhSGFd (B( (3Ke CJhLg (B) (3dJfHjg dWja jchf cGdTQM ddMajXI GdeYQhaI HMRH GdHMQ GdefShHg ddTjN CHj GdMSf GdTGPdi GdaUd GdChd ef GdebOeI ai MbjbI GdMRH s
(3BNQgG (B:s
(3hdPhi GdaVd hGdYde GdYPQ ai bHhdg hJMbjbg ef CUhdg hGddg ai Yhf GdYHO eG OGe GdYHO ai Yhf CNjg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B305s
Keywords: (3GdJUha hGdBOGH GdTQYjIs